The effect of social and environmental disclosure on companies’ market value - Husser, Jocelyn; Evraert-Bardinet, Frédérique (Management international / International Management / Gestiòn Internacional, 2014)
The research looks at the relationship between market value, accounting fundamentals and companies’ Corporate Social Responsibility (CSR) and Sustainable Development (SD) disclosures for the years 2007-2008. This article uses social and environmental scores derived from a structural analysis chart based on 120 companies’ reports. The results show that investors measure a company’s short-term performance using information about the quality of the company’s environmental management. At the same time, a company’s social disclosure concerning the quality of employee management influences short and long-term performance.